Self Reported Halitosis, Oral Hygiene Practices, Medical Conditions and Habits in OPD Patients of a Government Sector Institute in Karachi - Hina Taufeeq; Rizwan Nadim; Kashif Aslam; Shazia Akbar Ansari (Journal of the Dow University of Health Sciences, 2017)
Objective: To compare the difference of response in male and female patients associated with halitosis in relation to factors such as self reported halitosis, oral hygiene practices, medical conditions and habits. Methods: A cross section study was conducted at the OPD of a government sector institute Karachi. Samples of 400 participants were enrolled in the study. Data was collected through a formulated questionnaire and palm test. Statistically significant difference between males and females with respect to different factors was detected by Chi square test. Results: Factors which showed statistically significant result were “did you notice bad breath” (table1). “Tongue coated with deposits” brushing teeth everyday”, “use of mouthwash and floss everyday” (table 2). In table 3 “respiratory” and “GIT problems” were statistically significant while in table 4 only “mouth breathing” habit was statistically insignificant. Conclusion: Halitosis itself produces symptoms which could affect the social and personal interaction.